2017
DOI: 10.1161/strokeaha.117.016467
|View full text |Cite
|
Sign up to set email alerts
|

Silent Brain Infarctions and Leukoaraiosis in Patients With Retinal Ischemia

Abstract: Silent cerebral ischemia is present in about 1 in 7 patients with retinal ischemia. The high rate of symptomatic internal carotid artery stenosis suggests that large artery atherosclerosis plays a major role in the pathogenesis of acute retinal ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 14 publications
4
34
1
1
Order By: Relevance
“…In multiple recent studies it was reported that approximately 15% to 25% of patients with acute retinal ischemia have concurrent acute small cerebral infarctions on diffusion weighted imaging-MRI (DWI-MRI) (8,21,37,52,59,6164), despite the lack of other focal neurologic deficits at the time of presentation to suggest acute cerebral ischemia. Silent infarctions bear a high risk of future stroke; patients with acute silent cerebral infarctions and acute retinal ischemia most often have a major etiology identified, usually requiring urgent treatment to prevent a subsequent stroke (52,61,63,64).…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In multiple recent studies it was reported that approximately 15% to 25% of patients with acute retinal ischemia have concurrent acute small cerebral infarctions on diffusion weighted imaging-MRI (DWI-MRI) (8,21,37,52,59,6164), despite the lack of other focal neurologic deficits at the time of presentation to suggest acute cerebral ischemia. Silent infarctions bear a high risk of future stroke; patients with acute silent cerebral infarctions and acute retinal ischemia most often have a major etiology identified, usually requiring urgent treatment to prevent a subsequent stroke (52,61,63,64).…”
Section: Managementmentioning
confidence: 99%
“…Silent infarctions bear a high risk of future stroke; patients with acute silent cerebral infarctions and acute retinal ischemia most often have a major etiology identified, usually requiring urgent treatment to prevent a subsequent stroke (52,61,63,64). Therefore, all patients with acute retinal ischemia, even in the absence of other focal neurologic deficits, should have an immediate DWI-MRI of the brain to assess for concurrent cerebral ischemia.…”
Section: Managementmentioning
confidence: 99%
“…Data from previous studies support the use of long‐term monitoring for detection of atrial fibrillation as short‐term ECG monitoring of 1 day to 1 month is less effective 11,12,14 . There are limited data on the association of atrial fibrillation and CRAO 5,15–17 . Previous studies have advocated cardiac monitoring for as little as 24 hours to as long as 1 month post‐CRAO.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of AF in our cohort, although higher than expected is likely to be an underestimate, as almost 40% of patients did not have prolonged cardiac monitoring. Patients with symptomatic CAS and AF are at the highest risk for recurrent cerebrovascular ischaemia; indeed, recent studies showed that up to 20% of patients with monocular visual loss have concurrent silent cortical infarcts on MRI with patients having symptomatic CAS being at most risk [19, 20]. …”
Section: Discussionmentioning
confidence: 99%